Pengaruh Profitabilitas dan Leverage Terhadap Return Saham pada Sektor Energi Yang Terdaftar di Bursa Efek Indonesia - Gienah Terra Al Fache; Muhammad Iqbal Pribadi; Rahman Anshari (MANAJEMEN, 2025)
This study aims to examine the effect of profitability and leverage on stock returns in energy sector companies listed on the Indonesia Stock Exchange during the period 2019–2023. Profitability is proxied by Return on Assets (ROA), while leverage is measured by the Debt to Equity Ratio (DER). The population consists of 90 companies, from which 46 were selected using purposive sampling. The research uses secondary data obtained from annual financial statements. Panel data regression is employed as the analytical method. The results show that profitability (ROA) has a significant positive effect on stock returns, while leverage (DER) has a significant negative effect. These findings support the initial hypotheses of the study.